The effects of foot reflexology on back pain after coronary angiography: A randomized controlled trial. (February 2020) - Kardan, Mojgan; Zarei, Bahare; BahramiTaghanaki, Hamidreza; Vagharseyyedin, Seyyed Abolfazl; Azdaki, Nahid
Abstract: Background and aims: Back pain is among the most common complaints of patients during the first hours after coronary angiography (CA), i.e. when they are restricted to complete bed rest. This study aimed to evaluate the effects of foot reflexology on back pain after CA. Methods: This randomized controlled trial was conducted in 2018–2019 on patients hospitalized in the post-angiography unit of Razi hospital, Birjand, Iran. Through convenience sampling, 120 patients were recruited and their demographic characteristics and baseline back pain intensity were assessed immediately after angiography using a demographic questionnaire and a visual analogue scale, respectively. Then, patients were randomly allocated to a control (n = 60) and a reflexology (n = 60) group through block randomization. Patients in the reflexology group received 8-min foot reflexology for each foot (16 min for both feet) while their counterparts in the control group solely received routine post-angiography care services. Back pain assessment was repeated for all participants immediately, two, four, and 6 h after the intervention. Data were analyzed using the SPSS software (v. 16.0). Findings: Back pain intensity significantly increased after angiography in both groups (P < 0.05). Yet, pain intensity in the reflexology group at all post-intervention measurement time points was significantly less than the control group (P < 0.001). Conclusion: Foot reflexology is effective in significantly reducing back pain after CA. Highlights: Back pain is among the most common complaints of patients during the first hours after coronary angiography (CA). The effects of foot reflexology on back pain severity after CA was evaluated in this study. Pain intensity in the reflexology group at all post-intervention measurement time points was less than the control group. As an easy-to-use non-invasive technique, reflexology can be used to significantly reduce back pain after CA.